2002
DOI: 10.1016/s0925-4439(02)00080-7
|View full text |Cite
|
Sign up to set email alerts
|

Thymidylate synthase as a translational regulator of cellular gene expression

Abstract: Studies from our laboratory have shown that the folate-dependent enzyme, thymidylate synthase (TS), functions as an RNA binding protein. There is evidence that TS, in addition to interacting with its own TS mRNA, forms a ribonucleoprotein complex with a number of other cellular mRNAs, including those corresponding to the p53 tumor suppressor gene and the myc family of transcription factors. Using both in vitro and in vivo model systems, we have demonstrated that the functional consequence of binding of TS prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
89
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(94 citation statements)
references
References 63 publications
5
89
0
Order By: Relevance
“…These results indicate that the TS-and/or p53-high phenotype as determined by immunohistochemistry is a strong predictor of the resistance to S-1/cisplatin chemotherapy. Reportedly, TS forms a ribonucleoprotein complex with the p53 mRNA and the functional consequence of the binding is translational repression (Liu et al, 2002). In the lesions showing p53-low but TShigh phenotype (observed in five lesions of the nonresponders but in none of the responders), thus, TS may play a critical role in regulating the process of apoptosis through its regulatory effects on expression of p53.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that the TS-and/or p53-high phenotype as determined by immunohistochemistry is a strong predictor of the resistance to S-1/cisplatin chemotherapy. Reportedly, TS forms a ribonucleoprotein complex with the p53 mRNA and the functional consequence of the binding is translational repression (Liu et al, 2002). In the lesions showing p53-low but TShigh phenotype (observed in five lesions of the nonresponders but in none of the responders), thus, TS may play a critical role in regulating the process of apoptosis through its regulatory effects on expression of p53.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that TS forms a ribonucleoprotein complex with p53 mRNA (Liu et al, 2002). It is thereby suggested that TS may play a critical role in regulating the cell cycle and the process of apoptosis through its regulatory effects on the expression of p53.…”
mentioning
confidence: 99%
“…Unlike the protein response, hypoxia has been shown to have little effect on HIF-1a transcription in cell culture (Giaccia et al, 2003). Similarly, TS is mainly controlled at the translational level (Liu et al, 2002), which provides an energyefficient, rapid response to cellular stresses. However, we noted a sustained effect of ischaemia on TS and HIF-1a mRNA levels, highlighting the need for rapid preservation following tissue extirpation.…”
Section: Discussionmentioning
confidence: 99%
“…9 Second, the translation of TS mRNA is negatively autoregulated by the binding of TS enzyme to its mRNA. [10][11][12] This binding is disrupted when TS substrates or inhibitors are bound to the enzyme, leading to relief of translational repression and increased production of the enzyme. Finally, long-term exposure to TS inhibitors selects for cells in which TS is highly overproduced as a result of TS gene amplification.…”
Section: Introductionmentioning
confidence: 99%